Speech by the Hon'ble Enche D.C.Stewart at the Presentation Of Cattle And Goats at the Veterinary Department,Balik Pulau on 16th September, 1971. - Stewart, D.C. (1971)
I am very pleased to be with you this morning to hand over 6 buffaloes, 8 cows and 15 goats which are provided by the State under the Second Malaysia Rural Development Plan.